Suffering doubly: Effect of cyberbullying on interpersonal deviance and dual mediating effects of emotional exhaustion and anger - Syed, Nausheen; Hamid, Abu Bakar Abdul; Su, Xin; Bhatti, Misbah Hayat (Frontiers in Psychology, 2022)
Research on employee harassment, in the form of workplace bullying has been proliferated over the past decade. However, there is limited research on the incidence and impact of cyberbullying, a related type of cyber abuse in the work environment. Thus, it would be interesting to examine the impact of cyberbullying on interpersonal deviance through serial mediating effect of emotional exhaustion and anger. Drawing on conservation of resource theory and affective event theory proposed study clarifies the mediating effects of emotional exhaustion and anger. Time lag approach was used to collect the data from employees of telecommunication sector of Pakistan. By employing the SPSS & PLS, bootstrapping was performed to conduct the mediation analysis. Findings indicated that workplace cyberbullying increased the interpersonal deviance by enhancing the emotional exhaustion and anger. Current research contributes to the literature by considering the behavioral outcomes of workplace cyberbullying with the practical implications for human resource practitioners.